Parent‐Specific Transgenerational Immune Priming Enhances Offspring Defense—Unless Heat Stress Negates It All - Ralf F. Schneider; Arseny Dubin; Silke‐Mareike Marten; Olivia Roth (Ecology and Evolution)
ABSTRACT Transgenerational immune priming (TGIP) adjusts offspring's immune responses based on parental immunological experiences. It is predicted to be adaptive when parent–offspring environmental conditions match, while mismatches negate those advantages, rendering TGIP potentially costly. We tested these cost–benefit dynamics in the pipefish Syngnathus typhle (Syngnathidae). Because of their unique male pregnancy, egg production and rearing occur in different sexes, providing both parents multiple avenues for TGIP. Parental bacteria exposure in our pipefish was simulated through vaccinations with heat‐killed Vibrio aestuarianus before mating the fish to each other or to controls. The resulting offspring were exposed to V. aestuarianus in control or heat stress environments, after which transcriptome and microbiome compositions were investigated. Transcriptomic TGIP effects were only observed in Vibrio‐exposed offspring at control temperatures, arguing for low costs of TGIP in non‐matching microbiota environments. Transcriptomic phenotypes elicited by maternal and paternal TGIP had limited overlap and were not additive. Parentally induced transcriptomic responses were associated with immune functions, and specifically, the paternal response to the innate immune branch, possibly hinting at trained immunity. TGIP of both parents reduced the relative abundance of the experimental Vibrio in exposed offspring, showcasing its ecological benefits. Despite TGIP's significance in matching biotic environments, no TGIP‐associated phenotypes were observed for heat‐treated offspring, illustrating its limitations. Heat spikes caused by climate change thus threaten TGIP benefits, potentially increasing susceptibility to emerging marine diseases. We demonstrate the urgent need to understand how animals cope with climate‐induced changes in microbial assemblages to assess their vulnerability in light of climate change.